High-resolution body wave tomography beneath the SVEKALAPKO array: II. anomalous upper mantle structure beneath the central baltic shield ... - Sandoval, Senén; Kissling, Eduard; Ansorge, Joerg (ETH Zurich, 2004)
Geophysical Journal International, 157 (1) ... : ISSN:0956-540X ...